Experimental and numerical investigation for ductile fracture of Al-alloy 5052 using modified Rousselier model - Guo, Junhang; Zhao, Shengdun; Murakami, Ri-ichi; Zang, Shunlai (Computational Materials Science, 2013)
► We propose a modified Rousselier model by incorporating the extended damage evolution model of Nahshon and Hutchinson. ► The model parameters were calibrated by an FE based inverse method with smooth and notched round bars tensile tests. ► The model’s predictive ability in shear was improved by the Lode parameter. In this paper, the ductile fracture of Al-alloy 5052 is studied by experiments and simulations using a modified Rousselier model. Although tension failure has been successfully predicted by the classical Rousselier model, its predictive capability on shear failure was seldom discussed. A modified Rousselier model was proposed by incorporating the recent extended damage evolution model by Nahshon and Hutchinson. The modified Rousselier model can capture both tension and shear failure. A stress integration algorithm based on the general backward-Euler return algorithm for this constitutive model was developed and implemented into finite element model by the user defined material subroutine VUMAT in the ABAQUS/Explicit. The tensile tests of smooth round bar and notched round bars with different sizes were carried out to investigate the mechanical behavior of Al-alloy 5052. Consequently, the material parameters of the classical Rousselier model were identified by an inverse method using these experimental data. A shear test was also performed to calibrate the new shear damage coefficient in the modified Rousselier model. For the shear test, the simulations show that although shear failure can be predicted by the Rousselier model, the ductility was over-estimated. However, the modified Rousselier model can give more accurate results. The simulations on uniaxial tension of the round bars also confirm that the modified Rousselier model can well predict the cup-cone fracture mode. The results indicate that the Lode parameter in the new damage evolution model is important to capture the cup-cone fracture mode transition.